Exhibiting evangelicalism : commemoration and religion's presence of the past - Manzullo-Thomas, Devin C., 1987- (Public history in historical perspective., 2022)
"Religion is a subject often overlooked or ignored by public historians. Whether they are worried about inadvertent proselytizing or fearful of contributing to America's ongoing culture wars, many heritage professionals steer clear of discussing religion's formative role in the past when they build collections, mount exhibits, and develop educational programming. Yet religious communities have long been active contributors to the nation's commemorative landscape. Exhibiting Evangelicalism provides the first account of the growth and development of historical museums created by white evangelical Christians in the United States over the twentieth and twenty-first centuries. Exploring the histories of the Museum of the Bible, the Billy Graham Center Museum, the Billy Sunday Home, and Park Street Church, Devin C. Manzullo-Thomas illustrates how these sites enabled religious leaders to develop a coherent identity for their fractious religious movement and to claim the centrality of evangelicalism to American history. In their zeal to craft a particular vision of the national past, evangelicals engaged with a variety of public history practices and techniques that made them major players in the field-including becoming early adopters of public history's experiential turn"--